2016
DOI: 10.1037/pspa0000044
|View full text |Cite
|
Sign up to set email alerts
|

They see us as less than human: Metadehumanization predicts intergroup conflict via reciprocal dehumanization.

Abstract: Although the act of dehumanizing an outgroup is a pervasive and potent intergroup process that drives discrimination and conflict, no formal research has examined the consequences of being dehumanized by an outgroup-that is, "metadehumanization." Across 10 studies (N = 3,440) involving several real-world conflicts spanning 3 continents, we provide the first empirical evidence that metadehumanization (a) plays a central role in outgroup aggression that is (b) mediated by outgroup dehumanization, and (c) distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
423
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 285 publications
(470 citation statements)
references
References 84 publications
(169 reference statements)
45
423
1
1
Order By: Relevance
“…Although studying blatant dehumanization may be particularly important given the relationship to real-world outcomes (e.g., Kteily et al, 2016), it remains an open question as to whether these effects generalize to subtler measures of humanity. The primary goal of Study 2 was to test whether fWHR influences ascriptions of agency and experience.…”
Section: Studymentioning
confidence: 99%
“…Although studying blatant dehumanization may be particularly important given the relationship to real-world outcomes (e.g., Kteily et al, 2016), it remains an open question as to whether these effects generalize to subtler measures of humanity. The primary goal of Study 2 was to test whether fWHR influences ascriptions of agency and experience.…”
Section: Studymentioning
confidence: 99%
“…During the 2014 Gaza war, our sample of Israelis (members of the high power group) expressed extremely hostile attitudes towards Palestinians (members of the low power group), including the highest levels of blatant dehumanization towards any outgroup observed to date using the ‘Ascent of man’ measure of blatant dehumanization (i.e., higher than has been observed among American, English and Hungarian participants rating over two dozen different groups, including ISIS; [10], [33], [34]). Indeed, we found that Israelis rated Palestinians closer to an animal on the scale than to a ‘fully evolved’ human.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that Israelis rated Palestinians closer to an animal on the scale than to a ‘fully evolved’ human. This blatant dehumanization of Palestinians was also potent: even beyond subjective ratings of group power and ideological variables known to be strongly associated with intergroup hostility in this context (i.e., SDO and conservatism), dehumanization was uniquely associated with hostile attitudes likely to perpetuate cycles of intergroup conflict [29], [33], including unwillingness to negotiate, collective aggression and endorsement of massive civilian casualties. Interestingly, although we observed that the subjective perception of group power was weakly correlated with higher levels of blatant dehumanization, the association between dehumanization and outcomes was equally strong across levels of perceived power.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the unique contribution of blatant dehumanization to intergroup attitudes and behavior in concert with a range of other predictors. Previous work assessing the unique association between dehumanization and intergroup outcomes has included as parallel predictors measures of ideological orientation—including social dominance orientation (SDO; Esses, Veenvliet, Hodson, & Mihic, ; Kteily et al, ), right‐wing authoritarianism (Kteily et al, ), and political conservatism (Kteily et al, ; Kteily, Hodson, & Bruneau, ; Leidner, Castano, & Ginges, ; Maoz & McCauley, ), as well as measures of prejudice (Goff, Eberhardt, Williams, & Jackson, ; Goff, Jackson, Di Leone, Culotta, & DiTomasso, ; Jardina & Piston, ; Kteily & Bruneau, ; Kteily et al, ; Kteily et al, ). In the current research, we also include measures of political conservatism and affective prejudice.…”
Section: Previous Research On the Dehumanization Of Refugeesmentioning
confidence: 99%